Forest policies and forest resource flow in Burkina Faso, Ghana and Mali: conflicting or consistent for adaptation to climate change? - Kalame, F.B.; Idinoba, M.; Brockhaus, Maria; Nkem, J. (Center for International Forestry Research, 2008)
This policy brief analyses forest policies in Burkina Faso, Ghana and Mali and their implication for adaptation and conflicts under climate change. It presents results of studies undertaken by Tropical Forest and Climate Change Adaptation (TroFCCA). The policy brief tracks the flow of specific forest ecosystem goods and services and the potential for social conflicts in the form of disagreement. Divergent views, arguments and clashes are identified.